The Implication of Review on Arbitral Awards in the Legal Certainty of Construction Dispute Settlement - Kuswijanarko, Anjar; Sami’an; Hardjomuljadi, Sarwono (Journal of Law, Politic and Humanities, 2025)
Arbitration is a popular dispute resolution method in the construction industry in Indonesia because the process is fast, efficient, and the results are final and binding. However, attempts to retest or annul arbitral awards in courts often threaten the principle of finality. This study aims to analyze the legal basis for reviewing arbitral awards in Indonesia based on Articles 70-72 of Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, as well as its impact on legal certainty and efficiency in resolving construction disputes. Through a normative juridical approach and case studies, this study found that courts often annull arbitral awards on the grounds of forged documents, new evidence, or fraud (Hansen, 2019). Examples of cases such as PT. Hutama Karya vs PT. Krakatau Bandar Samudera show that annulment by the district court prolongs dispute resolution and adds to costs, which highlights the weakness of the arbitration system in Indonesia and can reduce trust in it. The study concluded that legal reform is necessary to limit the grounds for reviewing arbitral awards. Indonesia is also advised to establish a special arbitration court or a judge of construction dispute experts to increase legal certainty. Training and certification of arbitrators is necessary to reduce the potential for award errors, so that arbitration can be optimal as an effective and efficient method of dispute resolution.